Isolation and Identification of Fungal Propagation in Stored Maize and detection of aflatoxin B1 Using TLC and ELISA Technique - Hassan, Fadia; Al- Jibouri, Muna; Hashim, Abdul. Kareem (Iraqi Journal of Science, 2023)
Aflatoxin B1 (AFB1) is a mycotoxin produced mainly by fungi Aspergillus flavus in food and animals feed. It is considered as a carcinogenic toxin for human and animals. The current study is designed to investigate the incidence of mycoflora in twenty four samples of local stored maize collected from Iraqi governorates; investigate the presence of aflatoxin B1 on these samples using TLC and ELISA techniques. The fungi recovered from maize samples were Aspergillus flavus (18.57 % ), Fusarium spp. (12.8 % ), A. ocraceus (9.96 % ) , A. terrus (9.07 % ), A. fumigatus (8.46 % ) , Alternaria spp. (6.40 % ) Rhizopus spp. (4.98 % ), A. niger spp., A. oryzae spp. (4.80 % ), Penicillium spp. (4.53 %) A. versicolor spp., Rhizoctonia spp. (4.27 %), A. tamari and Mucor spp. (3.20 %). Aflatoxin B1 was present in twelve samples of stored maize collected from Iraqi governorate and the concentration of toxin ranged between 2.30 to 30 ppb using TLC technique and 270 to 500 ppb using ELISA technique.